ESPAUR Report 2021 to 2022 Chapter 5: NHS England Improvement and Assurance Schemes - Kieran Hand; Diane Ashiru-Oredope; Elizabeth Beech; Sabine Bou-Antoun; Gillian Damant; Naomi Fleming; Catherine Hayes; Philip Howard; Conor Jamieson; Monsey McLeod; Sejal Parekh; Preety Ramdut; et al. (Medical Sciences Forum, 2023)
NHS England designs and administers improvement and assurance schemes that include elements to incentivize prudent use of antimicrobials, optimise patient outcomes, minimise avoidable exposure to antimicrobials, and reduce selection pressure for antimicrobial resistance (AMR). These schemes include the NHS System Oversight Framework, the Pharmacy Quality Scheme for community pharmacies, the NHS Standard Contract, and the Commissioning for Quality and Innovation (CQUIN) framework. This report describes the schemes implemented from 2021 to 2022, and it reports the scheme performance of NHS commissioners and healthcare provider organisations. A summary of improvement and assurance schemes from 2022 to 2023 is also provided.